Regionalisation of Singapore firms : an eclectic review and analytical observation of the internationalising experiences of Singapore firms - Anil James Nathan Shukla (2010)
Between 1992 and 1993, the Singapore government officially formulated a regionalisation policy to encourage Singapore companies to invest overseas and to build an external economy that would enhance and create strong links with the domestic economy. This will help overcome inherent limitations such as lack of natural resources and manpower, tap on growing opportunities in the booming Asia-Pacific region and help forge closer ties with neighbouring countries. With this push, by the end of 1995, combined FDI of some 5,200 Singapore companies had increased to S$36.9 billion from S$13.6 billion in 1990.